Performance Characterization of Dosimeters Based on Radiation-Hard Silicon Diodes in Gamma Radiation Processing - Bueno, C. C.; Camargo, F.; Gonçalves, J. A. C.; Pascoalino, K.; Mangiarotti, A.; Tuominen, E.; Härkönen, J. (Frontiers in Sensors, 2022)
The dosimetric response of silicon diodes produced with distinct engineering technologies, Magnetic Czochralski (MCz), and standard Float Zone (Fz), has been investigated, aiming at their use for online dosimeters in gamma radiation processing applications. The p+-n-n+ junction diodes, 300 µm thick with an active area of 25 mm2, are operated as online radiation dosimeters in the short-circuit current mode. In this case, the key dosimetric quantity is the dose rate, which is correlated with the output current from the diode subjected to radiation. Thus, the dose is obtained offline by the integration of the corresponding current signal. The irradiations are performed with an industrial Gammacell 60Co facility at 2.5 kGy/h covering doses up to 275 kGy. Under continuous irradiation, both diodes delivered current signals whose intensities decrease with accumulated doses. Mitigation of this decay has been accomplished by pre-irradiating the devices to 700 kGy. Polynomial functions best represent the dose responses for either pristine or preirradiated diodes. The relevant dosimetric parameters as response stability, charge sensitivity, and repeatability of current signals (< 5%) reveal better performance of the MCz diode. It is important to note that the whole dataset fully complies with the international standard protocols for routine dosimeters in radiation processing dosimetry. Regarding radiation damage, which in unbiased diodes manifests primarily in the decay of current sensitivity, the results also showed greater tolerance of the MCz diode. Based on these studies, large availability, and better cost-effectiveness, it is possible to endorse the potential use of MCz devices as online routine dosimeters in radiation processing applications.